English Teachers’ Perception of Higher Order Thinking Skills Viewed from Importance and Complexity - Sukarni, Semi; Sudar, Sudar; Tarwiyah, Siti (FKIP Universitas Lampung, 2022)
English Teachers’ Perception of Higher Order Thinking Skills Viewed from Importance and Complexity. Objectives: This study aims at exploring the Vocational High School English teachers’ perception of its importance as well as its complexity of teaching HOTS. Methods: A mix-method approach of data collection and analysis was applied in this study. The data were obtained from 40 VHS teachers, the members of the English teacher association of Wonosobo regency, Central Java, Indonesia by using one set of close-ended questionnaires and in-depth interviews. Findings: The result indicates 1) VHS English teachers have a very high perception of the importance of teaching HOTS for their students; 2) a high perception of the complexity of applying HOTS resulted from the students’ unreadiness and teachers’ lack of competence in integrating HOT in English class. Conclusion: A very positive perception of the importance of teaching HOTS among VHS teachers. It is in constrast with the high perception of the complexity of applying HOTS. Training HOTS is needed for planning, implementing and assessing HOTS. Keywords: complexity, HOTS, importance, teachers’ perception, vocational high school.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202220